Transcend Urban Edges An Empirical Study on the Role of Teachers in Rural Education - Pandit, Unnat; Arahant, Arvind; Dash, Debendra Nath; Hoor, Adeeba; Prasad, Shivani (JOURNAL OF INDIAN EDUCATION, 2024)
Education is pivotal in shaping societies and individual growth, with teachers playing a central role in influencing student outcomes and educational quality. This study investigates the experiences, opportunities and challenges faced by teachers in Jhabua district of Madhya Pradesh, India and assesses their impact on education quality. Using qualitative methods, including observations and semi-structured interviews, data were collected from 25 teachers across three schools. Key themes identified include job satisfaction, teaching methods, technology integration, holistic development and educational challenges. Findings reveal that supportive environments and innovative teaching are integral to teacher satisfaction, thereby enhancing education quality. This research provides insights for stakeholders and policymakers, offering a basis for strategies to improve education in Jhabua by addressing challenges and fostering an inclusive and effective learning environment.